PENGARUH PENGGUNAAN METODE SHOW AND TELL TERHADAP KETERAMPILAN BERBICARA SISWA KELAS IV SD - Naibaho, Sarah Heirene; Faisal, F (Universitas Negeri Medan, 2024)
The purpose of this study is to find out whether or not there is an influence and effectiveness of the use of the show and tell method on the speaking skills of grade IV students of SDN 104208 Cinta Rakyat. This study is a quantitative research with pre-experimental design (nondesigns) and one group pretest posttest form. The research population is all grade IV students of SDN 104208 Cinta Rakyat totaling 65 people divided into three classes. The experimental class used is class IVB. The technique for determining samples is by purposive sampling, where samples are determined through certain requirements and criteria. Through data analysis, it was shown that the results of students' speaking skills were categorized as good, meaning that students' speaking skills were influenced by the show and tell learning method, which occurred due to the increase in the average score of students' speaking skills.Based on the average pre-test score obtained by grade IVB students, which was 43.35 and the average post-test score of 86.53, there was an improvement in speaking skills. Supported by hypothesis testing the t-test shows Asymp.Sig.( Two-Sided)= 0.001 is smaller than Î±=0.05. Through the N-Gain Test with the calculation of N-Gain, the minimum score of 0.60 and the maximum score of 1.00 resulted in a mean score of 0.7721 so that it is in the high or increasing category. Therefore, it can be concluded that the show and tell method has an effect and is effective on the speaking skills of grade IV students of SDN 104208 Cinta Rakyat.